Digital Democracy in America: A Look at Civic Engagement in an Internet Age. (March 2017) - Nelson, Jacob L.; Lewis, Dan A.; Lei, Ryan
Although the Internet has redefined interactions between the individual and the community, the U.S. civic engagement that so impressed Tocqueville still occurs today. Using data derived from a longitudinal survey of undergraduate students at a Midwestern university, we find that digital civic engagement fills the void left by drops in more conventional forms of political participation. We also find that educators have an important role to play in cultivating and maintaining online and offline civic engagement among younger people. We conclude that scholars and undergraduate educators need to develop curricula that build upon the ways students currently participate in democracy.